An Additive Effect of Oral N-Acetyl Cysteine on Eradication of Helicobacter pylori. (2nd September 2015) - Hamidian, Seyed Mohammad-Taghi; Aletaha, Najmeh-sadat; Taslimi, Reza; Montazeri, Mohammad
Abstract : Background. Helicobacter pylori is highly adapted to the gastric environment where it lives within or beneath the gastric mucous layer. The aim of this study was to evaluate whether the addition of N-acetyl cysteine to the treatment regimen of H. pylori infection would affect eradication rates of the disease. Methods. A total of 79 H. pylori positive patients were randomized to two therapeutic groups. Both groups received a 14-day course of three-drug regimen including amoxicillin/clarithromycin/omeprazole. Experimental group (38 subjects) received NAC, and control group (41 subjects) received placebo, besides three-drug regimen. H. pylori eradication was evaluated by urea breath test at least 4 weeks after the cessation of therapy. Results. The rate of H. pylori eradication was 72.9% and 60.9% in experimental and control groups, respectively (P = 0.005 ). By logistic regression modeling, female gender (OR 3.68, 95% CI: 1.06–5.79;P = 0.040 ) and treatment including NAC (OR 1.88, 95% CI: 0.68–3.15;P = 0.021 ) were independent factors associated with H. pylori eradication. Conclusion. The results of the present study show that NAC has an additive effect on the eradication rates of H. pylori obtained with three-drug regimen and appears to be a promising means of eradicating H. pylori infection.